Venetoclax: A First-in-Class Oral BCL-2 Inhibitor for the Management of Lymphoid Malignancies. (May 2017) - King, Amber C.; Peterson, Tim J.; Horvat, Troy Z.; Rodriguez, Mabel; Tang, Laura A.
Objective: To review the pharmacology, efficacy, and safety of venetoclax for treatment of lymphoid malignancies.Data Sources: A literature search was performed of PubMed and MEDLINE databases (2005 to September 2016), abstracts from the American Society of Hematology and the American Society of Clinical Oncology, and ongoing studies from clinicaltrials.gov. Searches were performed utilizing the following key terms: venetoclax, ABT-199, GDC-199, obatoclax, GX15-070, BCL-2 inhibitor, navitoclax, ABT-263, and Venclexta .Study Selection/Data Extraction: Studies of pharmacology, pharmacokinetics, pharmacodynamics, clinical efficacy, and safety of venetoclax in lymphoid malignancies were identified.Data Synthesis: Recently, treatment of B-cell lymphoproliferative disorders has shifted from conventional cytotoxic chemotherapy to novel small-molecule inhibitors. The advent of recently Food and Drug Administration–approved oral agents ibrutinib and idelalisib has shifted the paradigm of chronic lymphocytic leukemia (CLL) treatment; however, complete remission is uncommon, and the outcome for patients progressing on these treatments remains poor. Attention has been focused on a novel target, the B-cell lymphoma-2 protein (BCL-2), which serves an essential role in regulation of apoptosis. Venetoclax has demonstrated efficacy in multiple subtypes of lymphoid malignancies, including patients with relapsed/refractory CLL harboring deletion 17p, with an overall response rate of nearly 80%. Venetoclax is generally well tolerated, with the significant adverse effect being tumor lysis syndrome, for which there are formal management recommendations.Conclusion: Venetoclax has demonstrated promising results in relapsed/refractory lymphoid malignancies, with an acceptable adverse effect profile. As the role of BCL-2 inhibition in various malignancies becomes further elucidated, venetoclax may offer benefit to a myriad other patient populations.